Tinjauan Yuridis Sita Jaminan Hak Milik Pihak Ketiga (Studi Kasus No.28/PDT/2018/PT BGL) - Gitra Permata; Gustafianof Gustafianof (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Seizure of collateral (conservatoir beslag) aims to prevent the transfer of assets during the judicial process. Problems arise when the seized assets are claimed by a third party who is not directly involved in the dispute. This study analyzes the judge's considerations and the legal consequences of the decision of Case No. 28/PDT/2018/PT BGL on the rights of third parties. The Bengkulu High Court overturned the decision of the Bengkulu District Court and confirmed that the seizure of collateral remains valid, causing the third party (Siti Zahara) to lose her rights to the disputed land. The deed of agreement and power of attorney to sell that she owned were not recognized because they were not registered with the BPN. Other legal consequences are that the third party cannot file a re-claim (ne bis in idem), cannot change the name of the certificate, and bears the costs of the case. Legal efforts that can still be taken include a Judicial Review (PK) to the Supreme Court if there is new evidence, a PMH lawsuit, negotiation, or a complaint to the Judicial Commission and Ombudsman. In conclusion, the status of seizure of collateral is stronger than a claim of ownership based on a deed of agreement. Therefore, the third party must ensure the legality of ownership through official registration at the BPN in order to avoid legal problems.